Nonlinear Diffusion-Based Multifield Coupling Model for Thermally Enhanced CBM Recovery - Rui Yang; Weiqun Liu; Jiakun Lv (Geofluids)
Thermal stimulation is a supplementary technique for enhancing gas recovery from coalbed methane (CBM) reservoirs that has received considerable attention worldwide. Investigating gas and heat transfer in coal seams during thermally enhanced CBM recovery is of great significance for predicting gas production and optimizing the extraction method. Gas diffusion in the coal matrix and coupled multiphysics are two of the most important aspects when analyzing gas migration and heat transport. However, previous studies either neglected the nonlinear diffusion process of gas or only assumed that the diffusion coefficient varies with production time. However, considerable experimental results indicate that the gas diffusion coefficient is not only determined by time but also by temperature, which strongly impacts multifield interaction during gas recovery. Thus, prior diffusion models and coupled models must be modified. In this paper, a time-and-temperature-dependent gas diffusion model is established based on fractal theory and experimental data. The proposed diffusion model is embedded into the coupled thermal-hydro-mechanical model to comprehensively describe the behavior of coal deformation, gas migration, and heat transport during CBM recovery. Additionally, both new diffusion model and coupled model were validated with experimental results or field test data, showing that these developed models are applicable for modeling long-term gas diffusion and gas production. Finally, the coupled model was implemented into COMSOL Multiphysics software, and a series of numerical simulations were conducted. The calculation results showed that heat injection could promote gas desorption and diffusion in the matrix while inhabiting gas flow in fractures near the injection well. Gas dynamic diffusion could inhabit gas migration in both matrix system and fracture system at a later production stage. This also means that ignoring the gas nonlinear diffusion process leads to a severe overestimation of coal permeability and gas production.